2022
DOI: 10.1155/2022/4636618
|View full text |Cite
|
Sign up to set email alerts
|

Isosteviol Sodium Ameliorates Dextran Sodium Sulfate-Induced Chronic Colitis through the Regulation of Metabolic Profiling, Macrophage Polarization, and NF-κB Pathway

Abstract: Inflammatory bowel diseases (IBDs) constitute a group of chronic intestinal conditions prominently featuring deranged metabolism. Effective pharmacological treatments for IBDs are lacking. Isosteviol sodium (STV-Na) exhibits anti-inflammatory activity and may offer therapeutic benefits in chronic colitis. However, the associated mechanism remains unclear. This study is aimed at exploring the therapeutic effects of STV-Na against chronic colitis in terms of metabolic reprogramming and macrophage polarization. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…[16][17][18] Prior research have confirmed that STV-Na can reduce the activity of NF-κB/p65. 18 We therefore utilized a LPS-induced acute lung injury model and explored whether STV-Na has a potential therapeutic impact on lung injury and the intrinsic mechanisms associated with it. These documents demonstrate a potential basis for STV-Na treatment of ALI.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[16][17][18] Prior research have confirmed that STV-Na can reduce the activity of NF-κB/p65. 18 We therefore utilized a LPS-induced acute lung injury model and explored whether STV-Na has a potential therapeutic impact on lung injury and the intrinsic mechanisms associated with it. These documents demonstrate a potential basis for STV-Na treatment of ALI.…”
Section: Introductionmentioning
confidence: 98%
“…Despite this, there are not many studies on the potentiality of STV‐Na therapeutic effects for ALI 16–18 . Prior research have confirmed that STV‐Na can reduce the activity of NF‐ κB/p65 18 . We therefore utilized a LPS‐induced acute lung injury model and explored whether STV‐Na has a potential therapeutic impact on lung injury and the intrinsic mechanisms associated with it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing studies indicate that metabolic disorders modulate the pathogenesis of IBDs by regulating immune responses ( Aden et al., 2019 ; Lamb et al., 2022 ; Wang et al., 2022 ). Furthermore, glucose and lipid metabolism play important roles in T cells’ development and functions, even controlling the balance between Th17/Treg ( Qin et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…25 The different conjugated forms of isosteviol show anticancer activities and can thus be used for the synthesis of inexpensive chemotherapeutic agents. 26,27 Moreover, research on isosteviol has revealed that it shows peculiar DNA polymerase, DNA topoisomerase inhibition and acetylcholine inhibition abilities and antidiarrheal and antibacterial activities. [28][29][30] Another hydrolysate, sophorose, has not been directly applied for cellulase production by T. reesei to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%